2013
DOI: 10.5959/eimj.v5i3.146
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of medical students regarding educational climate at different phases of medical training in a Malaysian medical school

Abstract: Introduction: Medical and allied health educators around the globe agreed that an optimal educational climate is a vital aspect for effective learning to take place. Without a doubt, appraisal of the educational climate has been emphasized as a key to the delivery of high quality medical education. In addition, the appraisal provides useful feedback to particular institution to improve their curriculum. Objective: This study was employed as part of the School of Medical Sciences (SMS) Universiti Sains Malaysia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 40 publications
5
19
1
1
Order By: Relevance
“…The participants also accentuated the importance of having nurturing education environment during teaching. These are consistent with the previous study in this institution that showed clinical year students' rating is lowest in DREEM items "the teachers are authoritarian", "the teachers get angry in teaching" and "the students irritate the teachers" as compared to the younger batches (11).…”
Section: Theme 2: Teaching and Learning Strategiessupporting
confidence: 92%
See 2 more Smart Citations
“…The participants also accentuated the importance of having nurturing education environment during teaching. These are consistent with the previous study in this institution that showed clinical year students' rating is lowest in DREEM items "the teachers are authoritarian", "the teachers get angry in teaching" and "the students irritate the teachers" as compared to the younger batches (11).…”
Section: Theme 2: Teaching and Learning Strategiessupporting
confidence: 92%
“…Growing evidence shows an alarming trend of declining positive perception among clinical medical students towards the clinical education environment during medical training. The findings were consistent across different educational settings suggesting a universal struggle shared by most of medical students (3,(11)(12)(13). It was proposed that in clinical years, medical students are exposed to hidden curriculum, whereby they observed conflicting values in doctor-patient relationship, mistreatment to students and junior staffs and feeling unimportant in the workplace learning (3,12,14).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…There are many instruments available to measure the educational environment (Roff et al, ; Fraser, ; Chan, ). For instance, the educational environment related to the medical and allied health sciences field is commonly evaluated using the Dundee Ready Educational Environment Measure (DREEM; Roff et al, ; Al‐Hazimi et al, ; Varma et al, ; Arzuman et al, ; Yusoff et al, ). Although the DREEM has profound psychometric credentials established across different cohorts of undergraduate students of medical and allied health sciences, however, the items in DREEM reflect general construct of educational environment, and thus they may not cover certain important factors of the educational environment in a specific discipline.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical stage education is very likely to cause stress on students, because at that stage students are faced directly with the patient, having responsibility for being directly involved in patient care. Other research stated that the source of stress in the clinical stage students is clinical lecturers who on average act violently towards students [4]. Research conducted by Henning et al on fourth-year medical students also stated the same thing about quality of life.…”
Section: Discussionmentioning
confidence: 95%